One-month atogepant treatment induces rapid changes in delta-band functional connectivity in migraine: an HD-EEG study - Matteo Conti; Silvio Bagetta; Federico Carparelli; Valerio Ferrari; Vittoria Carla D’Agostino; Fabio Placidi; Alessandro Stefani; Nicola Biagio Mercuri; Maria Albanese (The Journal of Headache and Pain)
Abstract Background Atogepant is a novel oral calcitonin gene-related peptide (CGRP) receptor antagonist approved for the preventive treatment of migraine. While its peripheral mechanisms are well characterized, little is known about its potential effects on central functional brain networks. This study aims to investigate changes in resting-state functional connectivity (FC) using high-density EEG (HD-EEG) after one month of atogepant treatment in patients with migraine, and to assess the relationship between these changes and clinical response. Methods Twelve patients with high-frequency episodic migraine (HFEM; n = 7) or chronic migraine (CM; n = 5) underwent HD-EEG recordings at two time points: before starting Atogepant administration (T0) and after one month of treatment (T1). Fifteen healthy controls (HC) were also enrolled. Clinical evaluations included: monthly migraine days (MMD), monthly symptomatic drugs intake (MSI), modified Migraine Disability Assessment (mMIDAS), the headache impact test (HIT-6), the Migraine-Specific Quality of Life Questionnaire (MSQ), the 12-item Allodynia Symptom Checklist (ASC-12), and the Migraine Interictal Burden Scale (MIBS-4). EEG-based FC was analyzed in source space using the weighted Phase Lag Index (wPLI) across δ, θ, α, β, low-γ, and high-γ bands. To identify changes related to treatment, we applied Network-Based Statistics (NBS), while Spearman correlation was used to explore the relationship between clinical improvements and functional changes. Results Compared to HCs, HFEM + CM patients exhibited increased δ band functional connectivity (FC) in temporo-parietal, orbitofrontal, insular, and limbic regions. After one month of atogepant treatment, a significant reduction in this aberrant FC was observed, particularly in bilateral temporo-parietal, cingulate, insular, and prefrontal cortices. Baseline δ-band FC correlated with greater clinical disability (mMIDAS, MSQ), while treatment-induced FC changes (ΔmNC) were associated with improvements in mMIDAS, HIT-6, and ASC-12 scores, highlighting the clinical relevance of δ band network modulation. Conclusions This pilot study provides preliminary evidence that atogepant modulates δ band functional brain connectivity after one month of treatment in patients with episodic and chronic migraine. These changes in central brain networks are associated with clinical improvement and may serve as a neurophysiological marker of CGRP receptor antagonist efficacy. Larger-scale studies are needed to confirm and extend these findings.